Measuring leadership development quantify your program's impact and ROI on organizational performance - Phillips, Jack J. 1945-; Phillips, Patti; Ray, Rebecca (McGraw-Hill, 2012)
Developing an understanding of the application and impact of leadership development efforts is required to make informed choices. This title provides an assessment that every leadership development practitioner should use to develop and enhance their efforts to support the strategic growth of their company.